Prototyping a stable pulse oximeter - Ng, Christine. (2011)
Pulse oximeter has become an essential medical device in the modern practice of emergency department in a hospital for its ability to provide convenient, non-invasive and continuous monitoring of oxygen levels in a human body (1). By constructing the pulse oximeter from scratch, the author was able to build a highly customizable pulse oximeter in terms of functionality. Implementing LabVIEW in operating this pulse oximeter provides superior versatility in modification process.